Development of tactile sensors for simultaneous, detection of normal and shear stresses - Huang, Yu-Ming; Tsai, Nan-Chyuan; Lai, Jing-Yao (Sensors and actuators. A. Physical., 2010)
A novel tactile sensor is analyzed and verified by intensive experiments. By using micro-cantilever beams, on which the strain gauge layers (Pt/Ti) are deposited, the corresponding induced strains can be detected and converted into electric resistance change, with respect to either applied normal stress or shear stress. The four micro-cantilever beams are allocated in the fashion such that any adjacent beams are perpendicular to each other to decouple any potential measurement discrepancy due to non-ideal orthogonality. In addition, the micro-cantilever beams are curled beforehand so that they can concurrently detect normal stress and shear stress. To be protected from being damaged by strong stress, the curled cantilever beams are embedded by elastomer material. Therefore, the micro-tactile sensor can detect normal stress up to 250 kPa and shear stress up to 35 kPa. Besides, since the elastomer is made of PDMS, which is of high bio-compatibility, the tactile sensor can be used to directly contact with human body. By taking the design and fabrication parameters into account, the curled micro-cantilever beams, which are composed by four layers: polymer/Pt/Ti/Si, can be produced with high yield rate. Finally, the efficacy of the tactile sensor is verified by experiments via a micro-manipulator, a high-resolution microscope and a force sensor for calibration.